Does country environment matter in the relationship between intellectual capital and innovation performance? - Andreeva, Tatiana; Garanina, Tatiana; Sáenz, Josune; Aramburu, Nekane; Kianto, Aino (Elsevier, 2021)
This paper examines how country environment shapes the relationship between firm intellectual capital and its innovation performance. Using survey data from 649 firms in Finland, Spain and Russia complemented by archival IMD World Competitiveness Ranking data, we find that when country environment is characterised by greater availability of skilled labour and a stronger appropriability regime, a firm’s human and structural capital have a lower impact on its innovation performance. The effect of relational capital does not depend on these contextual variables. This study enriches the intellectual capital-based view of the firm by demonstrating that country-level factors moderate the performance effects of firm-level intellectual capital. It also adds to the strategic management literature by exploring the explanatory power of a combination of country-level variables and firm-level resources in understanding firm-level performance. Our findings can help practitioners focus on the elements of intellectual capital that have the greatest impact in their environment.
Keywords: Intellectual capital; Home country environment; Appropriability regime; Institutions; Factor markets; innovations; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|